Evaluation of Gait-Assistive Soft Wearable Robot Designs for Wear Comfort, Focusing on Electroencephalogram and Satisfaction - Yoon, Jeong Eun; Chung, Jiwon; Park, Soah; Won, Hyunbin; Kim, Changhwan; Baek, Inryeol; Koh, Je Sung; Koo, Sumin Helen (IEEE Robotics and Automation Letters, 2024)
Wearable robots should be comfortable; however, there is lack of research on wear comfort for wearable robots has been conducted. This study aimed to evaluate the comfort of wearable soft robot platforms designed for walking assistance. We proposed clothing-based wearable robot platforms that prioritized wearer comfort to contribute to the advancement of a more human-centered wearable robot. Two designs, Design 1 (pant-type) and Design 2 (suit-type), were used to analyze the comfort of wearing the developed wearable robot platforms for gait assistance, using electroencephalogram (EEG) measurements and post-wear satisfaction evaluation. Design 2 revealed more comfort data than Design 1 when walking; thus, enhancing people's satisfaction. The findings can contribute to the development of comfortable soft wearable robots, thereby enabling people to walk without difficulty in their daily lives.
Keywords: Assistive; Clothing; Legged locomotion; Robot designs; Robot platform; Robot sensing system; Soft robot; Walking assistance; Wear comfort; Wearable robots; Actuators; assistive devices; fabrics; wearable devices; wearable robots